Pixelated bifunctional metasurface-driven dynamic vectorial holographic color prints for photonic security platform - Inki Kim (Nature Portfolio, 2021)
The authors present a bi-functional metasurface, combining structural color printing observed under white light and polarization encoded It is appropriate. vectorial holography. A pixelated design is used encode multiple holographic images, and they demonstrate an electrically tunable optical security platform.